Facility-level comorbidity burden and cardiovascular outcome in patients undergoing hemodialysis - Hyo Jeong Kim; Seok-Jae Heo; Jung Tak Park; Ga Young Heo; Kyung Won Kim; Yong Uk Kwon; Soo Hyun Kim; Gui Ok Kim; Seung Hyeok Han; Tae-Hyun Yoo; Shin-Wook Kang; Hyung Woo Kim (Kidney Research and Clinical Practice, 2026)
Background: The impact of facility-level comorbidity burden on the prognosis of hemodialysis patients remains unclear. This study aimed to investigate the association between facility-level comorbidity burden and hemodialysis outcomes. Methods: We examined 15,481 participants receiving hemodialysis at primary clinics participating in the Periodic Hemodialysis Quality Assessment by Health Insurance Review and Assessment Service in Korea. Facility-level comorbidity burden, defined as the sum of the Charlson Comorbidity Index of all patients divided by the number of nurses in each hemodialysis center, was the primary predictor. The primary outcome was major adverse cardiac and cerebrovascular events (MACCE). Results: During a median follow-up of 6.8 years, MACCE and all-cause mortality occurred in 9,797 (63.3%) and 8,513 participants (55.0%), respectively. Participants in the highest facility-level comorbidity burden had the highest incidence rates of both MACCE and all-cause mortality. Hazard ratios (HRs) of MACCE and all-cause mortality in the highest vs. the lowest quartile were 1.10 (95% confidence interval [CI], 1.03–1.18) and 1.14 (95% CI, 1.06–1.22), respectively. Applying the facility-level comorbidity burden as a continuous variable, each 10-unit increase in facility-level comorbidity burden was associated with a 4% and 8% higher risk of MACCE and all-cause mortality, respectively. These associations remained consistent across subgroups. Conclusion: Our findings revealed that the facility-level comorbidity burden in hemodialysis centers was associated with a higher hazard of poor outcomes in patients undergoing hemodialysis.